New approach methodologies for risk assessment of urinary occurring toxicants - Maximilian Jobst; Irís Guerreiro; Delphine Payros; Isabelle P. Oswald; Ana S. Fernandes; Benedikt Warth; Giorgia Del Favero (Ecotoxicology and Environmental Safety)
The reduction, refinement, and replacement of animal-based toxicological studies is becoming an essential requirement at academic, industrial, and governmental levels, turning new approach methodologies (NAMs) from alternatives into necessities. New strategies for hazard characterization and exposure assessment have been developed in this wake, including among others, sophisticated organ-on-chip platforms, or holistic human biomonitoring programs. This review summarizes state-of-the-art methods of NAMs for hazard characterization and advances in exposure assessment in the context of toxicants occurring in human urine. Considering that urine collects a wide variety of excretion products, it can harbor chemically diverse compounds including heavy metals and metalloids, foodborne mycotoxins and phytotoxins, as well as synthetic and process chemicals. Hence, urine analysis is a precious element for exposure assessment and the urinary excretory organs are highly relevant toxicological targets. Especially for environmental or foodborne contaminants, the classical regulatory framework is challenged by natural variability of the producing organisms, climate change, global trade, and obviously heterogeneous exposure landscape related to an individual’s lifestyle and diet. In this light, NAMs represent an unprecedented opportunity to support and speed up risk assessment. The aim of this review is to summarize current knowledge, in order to identify gaps on hazard profiling for selected urinary occurring contaminants, as well as for their exposure assessment. Furthermore, it aims at identifying the challenges in the field from both the toxicological and analytical perspectives in light of next generation risk assessment (NGRA).